Penerapan BMS pada Baterai Lithium-ion Sebagai Balancing Pengisian dari Panel Surya pada Siswa SMKN 1 Tengaran - Hilal, Yusuf Nurul; Pinandita, Satria; Sadewa, Ery (Muria Jurnal Layanan Masyarakat, 2024)
The 18650 type lithium-ion battery is the type of battery most widely used in today's era, such as in electric cars, electric saws, electric drills and many more. This battery was chosen because it has stable performance, is more environmentally friendly and has a longer service life compared to other types of batteries. However, in use, lithium-ion batteries cannot stand alone, these batteries require an additional circuit, namely the BMS (battery management system), which functions to protect the battery from over charging, over discharging, short and over temperature, so that it is safe to use. Community service was carried out at SMKN 1 Tengaran, Semarang Regency, by providing material and training regarding the use of BMS on lithium-ion batteries by charging them using solar panels. This training was carried out for 3 hours with a total of 30 students, starting from delivering the material to direct practice.